Air Polution Causes Some Problems for Traders in Amplas Terminal - Dinda Aljarina; Sri Malem; Nurmaini Nurmaini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine and analyze the relationship between carbon monoxide levels and health complaints on Traders at Amplas Terminal. This study uses an analytical survey method with a cross-sectional study design. The population in this study were All Traders who carried out trading activities at the Amplas Terminal, as many as 53 people. Samples of air pollution from carbon monoxide gas located at the center of pollution by transportation and based on points of location where trading is at the Amplas Terminal. The data analysis method in this study used bivariate analysis. The results showed that there was no relationship between carbon monoxide levels and health complaints on Traders at Amplas Terminal.